2021
DOI: 10.1016/j.jmig.2021.01.022
|View full text |Cite
|
Sign up to set email alerts
|

vNOTES Hysterectomy with Sentinel Lymph Node Mapping for Endometrial Cancer: Description of Technique and Perioperative Outcomes

Abstract: To explore the technique and clinical value of transvaginal natural orifice transluminal endoscopic surgery (vNOTES) in hysterectomy and sentinel lymph node (SLN) mapping for endometrial cancer by comparing its perioperative outcomes with those of laparoscopic staging. Design: Retrospective cohort study. Setting: Department of gynecology at a tertiary medical center. Patients: All women diagnosed with endometrial cancer who underwent minimally invasive surgery at our center between August 2017 and May 2020. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 27 publications
0
44
1
Order By: Relevance
“…6 A retrospective study from China showed that the vNOTES procedure is feasible, with a potentially shorter post-operative hospital stay, faster recovery, and better cosmetic results in patients with endometrial cancer. 7 The retroperitoneal vNOTES procedure has the advantage that it can be used in patients with endometrial cancer to avoid bowel injury during entrance to the abdominal cavity, both in patients with a previous midline incision and in those undergoing first surgery. The difficulty of correctly getting within the bilateral retroperitoneal spaces was the factor determining the appropriate site of vaginal incision, use of blunt dissections to reach the obturator fossa, and placement of the device.…”
Section: Video Articlementioning
confidence: 99%
“…6 A retrospective study from China showed that the vNOTES procedure is feasible, with a potentially shorter post-operative hospital stay, faster recovery, and better cosmetic results in patients with endometrial cancer. 7 The retroperitoneal vNOTES procedure has the advantage that it can be used in patients with endometrial cancer to avoid bowel injury during entrance to the abdominal cavity, both in patients with a previous midline incision and in those undergoing first surgery. The difficulty of correctly getting within the bilateral retroperitoneal spaces was the factor determining the appropriate site of vaginal incision, use of blunt dissections to reach the obturator fossa, and placement of the device.…”
Section: Video Articlementioning
confidence: 99%
“…To allow the port to stay in place vaginally, the authors [7] also recommended completion of the anterior repair prior to the HUS ligament suspension, a change in the order of the flow compared to what is done traditionally. In the retrospective cohort study by Wang et al [9], this early experience with vNOTES hysterectomy and SLN was found to be comparable in perioperative outcomes to laparoscopy.…”
mentioning
confidence: 93%
“…These span initially from simple procedures such as salpingectomy, ovarian cystectomy, oophorectomy, and hysterectomy for benign indications, to now more complex procedures for urogynecologic and oncologic applications. In this issue, we feature three papers with accompanying videos that demonstrated the incorporation of vNOTES after conventional VH to facilitate what can be difficult transvaginal procedures -the high uterosacral ligament suspension (HUS) [7], sacrocolpopexy [8] for prolapse and sentinel node dissection (SLN) for early-stage endometrial cancer [9]. Many helpful tips and nuances to the vNOTES technique that come aptly from experienced surgeons were highlighted.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, vNOTES has been increasingly applied to perform benign gynecologic procedures such as hysterectomy, myomectomy, several adnexal procedures, uterosacral ligament suspension, and sacrocolpopexy (14)(15)(16). To date, the role of vNOTES in gynecological oncology still requires evaluation, as only a few studies have reported on it (17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%